THE USE OF A BIODEGRADABLE SELF-EXPANDABLE PROSTHESIS AS A SOLUTION FOR COLORECTAL ANASTOMOSIS STENOSIS - Fagoso, Marta (2023)
Benign colorectal strictures are usually treated by endoscopic dilation. The use of metallic stents is limited and not clear. Biodegradable stents initially developed for management of refractory esophageal benign strictures have an important advantage as they do not need to be removed. However, their use is yet to be validated in intestinal strictures. We report a case of a 25-year- old woman, with a sigmoid volvulus who underwent colonic resection, complicated by early anastomotic stricture. A new surgery and anastomosis were performed, and early recurrence occurred. A biodegradable stent was applied, with no complications or recurrence during 5-years follow-up. Additional studies are recommended to establish the long-term safety and efficacy of this procedure.